The Influence of Modernization on the Essence of Thanksgiving in Minahasa Society - Veronike E.T Salem,; Ferdinand Kerebungu,; Hamsah Hamsah,; Cahyadi Nugroho,; Awaluddin Hasrin, (Technium Education and Humanities, 2024)
This study aims to analyze the influence of modernization on the essence of gratitude in Minahasa society. The main focus is to identify changes that occur in the practice, meaning, and social function of this ritual, as well as to explore the adaptation strategies developed by the community in maintaining tradition amidst the flow of modernization. The method used is a qualitative approach with literature review techniques. This study analyzed various sources of academic literature, including journal articles, books, and relevant research reports, published in the last 20 years. Data analysis was carried out using a thematic analysis approach to identify patterns and main themes from the literature reviewed. The results of the study indicate that modernization has brought significant changes to the Minahasa gratitude ritual, including a shift in motivation from spiritual to socio-economic, the transformation of ritual practices with the use of modern technology, changes in community participation, and the emergence of new challenges in preserving the essence of the ritual. However, the study also revealed cultural resilience, where the Minahasa community actively developed adaptation strategies to maintain the core values of the ritual while adapting to the demands of modernity. These findings provide important insights into the dynamics between tradition and modernity in the context of local culture, as well as their implications for efforts to preserve cultural heritage in the global era.